2020
DOI: 10.3389/fchem.2020.00140
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High-Performance CdS@C Catalyst Using Cd-Enriched Biochar Recycled From Plating Wastewater

Abstract: Biochar is widely used for the adsorptive removal of Cd from water and soil, but the Cd-enriched biochar produced carries a risk of secondary pollution. In this work, biochar derived from rice straw was used to adsorb Cd from plating wastewater. The Cd-enriched biochar showed a saturated adsorption capacity of about 63.5 mg/g and could be recycled and used in a mesoporous carbon-supported CdS (CdS@C) photocatalyst after pyrolysis carbonization and a hydrothermal reaction. The results demonstrated that the as-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 53 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Cd catalysts aimed for photodegradation of water pollutants down to permissible levels were prepared [42]. Xing et al [43] provided an alternative use of metal-contaminated streams when they demonstrated that vegetal biochar can be transformed with plating wastewater into reusable Cd-biochar acting as nano Cd-S with photocatalytic activities and tested the concept in dye removal from water.…”
Section: Thermochemical Treatmentsmentioning
confidence: 99%
“…Cd catalysts aimed for photodegradation of water pollutants down to permissible levels were prepared [42]. Xing et al [43] provided an alternative use of metal-contaminated streams when they demonstrated that vegetal biochar can be transformed with plating wastewater into reusable Cd-biochar acting as nano Cd-S with photocatalytic activities and tested the concept in dye removal from water.…”
Section: Thermochemical Treatmentsmentioning
confidence: 99%
“…Xing et al 128 utilized rice straw as a carbon source and Cd-containing plating wastewater as a Cd source to fabricate a CdS@C photocatalyst via facile pyrolysis carbonization and a hydrothermal process (see Fig. 13a ).…”
Section: Green Photocatalysts For the Photodegradation Of Various Pol...mentioning
confidence: 99%
“…Adsorption is one of the most effective methods to treat organic dyes, and it is widely used because of its relatively low cost and easy operation. Various adsorbents have been designed to remove dyes in water and have considerable adsorption capacities, such as activated carbon ( Tang et al, 2017 ; Zhang et al, 2019 ; Soares et al, 2021 ), functional carbon materials ( Magno et al, 2020 ; Xing et al, 2020 ; Zhang et al, 2020 ), composite hydrogel ( Srivastava and Roy Choudhury, 2021 ), and metal oxide ( Rastogi et al, 2017 ; Xu et al, 2020 ; Şerban and Enesca, 2020 ). Among these methods, chemistry reduction has gained popularity because of its ease of use, high efficiency, clean processing, and low cost.…”
Section: Introductionmentioning
confidence: 99%